Desenvolvimento de conversores de cinco níveis com capacitor chaveado e grampeamento ativo do ponto neutro - Castiblanco, Wilmar Armando Pineda (2022)
This work aims to propose a five-level converter topology. The proposed converter uses the switched capacitor concept with an active neutral point clamped structure, with one floating capacitor per phase and only one dc-link, even in three-phase systems. When operated as an inverter, the proposed converter synthesizes similar output voltages compared to traditional five-level inverters, but with a reduction of the input dc-link voltage at half. Some benefits can be highlighted, such as: reduction of voltage especification in the semiconductors and capacitors and, consequently, minimization of the total standing voltage of the circuit. In order to facilitate the floating capacitor voltage control, a modulation strategy based on the switched capacitor principle is also explored. Thus, voltage regulation occurs automatically without any control strategies and/or the use of additional circuits and sensors. However, although the complexity of the voltage balance is reduced, it increases the currents stress in the components, usual in switched capacitor based circuits, so a current analysis is introduced. Additionally, the proposed converter is operated as a unidirectional rectifier. In this case, the number of active semiconductors and associated drive circuits can be reduced by half. The modulation strategy also allows the automatic voltage balance in the floating capacitors, which simplifies the operation of the system connected to the three-phase grid. Simulation and experimental results are included to show the functionality of the proposed converter.